Alteritatea ființei prin limbaj și semnul lingvistic în concepția Sfântului Augustin - Cristian PAȘCALĂU (Eon)
The current essay is meant to revisit a core theme in the philosophy of language, namely the role of the subjectivity and alterity in shaping human consciousness through language and linguistic signs, associated with the understanding of reality as inner construct in the fabric of human mind. A loose critic against some paradigms that reduce language to a means of communication, or an abstract, logical device is provided. We also briefly examine Saint Augustine’s semiotic project, as it unfolds from some of his most seminal works.